Patterns and correlates of new psychoactive substance use in a sample of Australian high school students. (21st July 2015) - Champion, Katrina E.; Teesson, Maree; Newton, Nicola C.
Abstract: Introduction and Aims: In recent years there has been growing concern about new psychoactive substances (NPS) designed to mimic the effects of established illicit drugs. This paper explores the patterns and correlates of NPS use in a sample of Australian students. Design and Methods: A cross‐sectional survey was conducted in Australia in 2014. Data were collected from 1126 students (mean age: 14.9 years) from 11 secondary schools. Students completed a self‐report questionnaire assessing NPS use and knowledge, beliefs and intentions to use these substances. NPS users were compared with non‐users and illicit drug users, who had not used NPS, in terms of gender, binge drinking, tobacco use, psychological distress and self‐efficacy to resist peer pressure. Results: Of the 1126 students, 3% reported having ever tried NPS, 2.4% had used synthetic cannabis and 0.4% had used a synthetic stimulant. Analyses revealed that NPS users were more likely to have had an episode of binge drinking in the past 6 months, tried tobacco and had higher levels of psychological distress and lower perceived self‐efficacy to resist peer pressure than non‐users, but did not significantly differ from users of other illicit drugs. Discussion and Conclusions: NPS use appears to be uncommon among Australian school students. Although adolescents that do use these substances did not differ from students that had used traditional illicit drugs, both appear to be higher‐risk groups of students than non‐users. Our findings suggest that universal education about NPS be incorporated into existing drug prevention programmes, and that targeted NPS prevention may also be warranted among high‐risk adolescents. [Champion KE, Teesson M, Newton NC. Patterns and correlates of new psychoactive substance use in a sample of Australian high school students . Drug Alcohol Rev 2016;35:338–344]